Model Inovasi Pengembangan Media Belajar Pendidikan Agama Islam di Raudhatul Athfal (RA) - Warosari, Yuli Fatimah; Sari, Maya Inayati; Damayanti, Efrida; Murhayati, Sri (STAI Auliaurrasyidin Tembilahan, 2024)
The era of globalization requires RA teachers to be able to innovate their knowledge with science and technology in digitizing education. This study aims to obtain data on the innovation model of learning media development, with a focus on the use of digital technology in improving digital literacy for children, especially in the context of learning Islamic Religious Education materials in Raudhatul Athfal (RA). This research is a qualitative study using a literature study approach that examines various scientific references, such as journals, books and e-books that are relevant to the topic of discussion within the scope of the role of technology-based learning media in learning Islamic Education in RA and digital literacy. The data were then analyzed by comparing the related journals and combining them to be relevant data. The results showed that the utilization of technology as a medium of learning Islamic Education in RA has a great influence on the paradigm of Islamic learning. Thus, this requires teachers to be able to innovate their knowledge in using digital media to develop learning with the hope that motivation, learning outcomes, and digital literacy in students can increase.